(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
Accessions of Colocasia esculenta L. Schott. cultivars collected from thirteen aroid growing districts were studied for determining their genetic variability under the agromorphological purviews. Plant height, petiole length, petiole breadth, leaf number, leaf length, leaf breadth, LAI, inflorescence length, peduncle length, spathe length, spathe breadth, corm length, corm breadth, cormel number, cormel length, cormel breadth, corm weight, cormel weight, total fresh weight, total dry weight, yield per plant were taken in this study for nature and extent of variability analysis of edible cultivars of Colocasia esculenta L. Schott. Presence of significant differences together with wide ranges of variation in most cultivars indicates wide range of variability existed among the accession as well as local cultivars of this edible aroid. Genotypic variances and coefficient of variation for most of the characters were remarkably higher than their corresponding environmental variances which also indicate the existence of variation in genotypic origin. Key words: Characterization; Mukhikachu; Variability; Corm; Cormel; Colocasia esculenta. DOI: http://dx.doi.org/10.3329/bjsir.v46i2.8191 Bangladesh J. Sci. Ind. Res. 46(2), 235-242, 2011